Investigating the PROMIS Physical Function and Pain Interference Domains in Elite Athletes. Issue 1 (29th December 2021) - Franovic, Sreten; Schlosser, Collin; Guo, Eric; Hessburg, Luke; Kuhlmann, Noah A.; Okoroha, Kelechi R.; Makhni, Eric C.
Background: Multiple studies have demonstrated the National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) to be a responsive and efficient measure for patients undergoing orthopaedic surgery. While these studies were rigorous in their protocol and methodology, no efforts in recent literature have been made to identify if these reference scores apply to elite athletes. Purpose/Hypothesis: The purpose of this study was to determine whether there is a difference in the baseline scores of elite athletes versus the general population. We hypothesized that athletes' PROMIS upper extremity general function (PROMIS-UE) and general physical function (PROMIS-PF) scores would vary substantially from the mean health state of the general population. We further hypothesized that these scores would be affected by specific sport and level of competition Study Design: Cross-sectional study; Level of evidence, 3. Methods: Three PROMIS computer adaptive test (CAT) domains were administered to elite athlete (≥18 years) volunteers (either in person or through email). An elite athlete was defined as one participating in sports at the collegiate level or higher. Test domains included PROMIS-PF, PROMIS-UE, and pain interference (PROMIS-PI). PROMIS domain t scores were defined and assessed against NIH reference values to identify significant differences. Distribution analysis was conducted using histograms and normality assessments. Domains were also subject to correlation analysis. Finally, subgroup analysis was conducted for all athlete characteristics to identify any factors associated with variance. Results: In total, 196 elite athletes (mean age, 21.1 years; range, 18.0-36.7 years) completed all 3 PROMIS-CAT forms. Overall, the mean scores were 56.0 ± 6.4, 58.1 ± 7.7, and 47.1 ± 7.3 for PROMIS-UE, PROMIS-PF, and PROMIS-PI, respectively. Distribution analysis showed nonnormal distribution for all 3 PROMIS domains (Kolmogorov-Smirnov test, P < .001). Similarly, in all 3 PROMIS domains the athletes displayed more disparate scores than the NIH-reported reference values (1-way sign test, P < .001). Only the presence of pain and sport played showed association with variance in PROMIS domain scores ( P < .001 and P = .003, respectively). Conclusion: Elite athletes displayed more disparate reference scores than the NIH-reported average of 50 for PROMIS-UE, PROMIS-PF, and PROMIS-PI. Furthermore, these forms were sensitive to varying levels of sport among collegiate athletes.